Solusi Numerik Metode Beda Hingga Aplikasi Excel Untuk Solusi Lendutan Balok Beton Sederhana - Wahyo Hendarto Yoh (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2017)
The use of worksheets in Excel is one of the tools for learning in solving the mathematical problems. At generaly the solution of mathematical problem ussually is solved by the soft ware aplication, that sure used high level programming languages like FORTRAN, BASIC, C++, MATLAB, etc. However the use of worksheet in Excel rather more familiar than using the software aplication for the students. It is caused the students must be able to know how to write the code program that obtained product the listing program. One of the most problematic on civil engineering is about concrete beam structure deflection. The mathematical analysis simple beam structure deflection is presented by the ordinary differential equation second order non linier and the other name it’s called poisson equation. The aim of this article for : (1) To give the learning assistance to the student when they aren’t use the soft ware program and beside to rise creation the application spreadsheet as tool for numerical solution by finite difference method on simple beam deflection. (2) To evaluate the error result comparation of numeric solution and analytic solution.(3)To give the understanding about numerical method that accordance with simple beam deflection problem on civil engineering education and mathematical education. Keywords: Fungsi Internal EXCEL, Metode Beda Hingga. Persamaan Garis Elastika.